KUALITAS PRIBADI KONSELOR: URGENSI DAN PENGEMBANGANNYA - Fuad, Muskinul (Fakultas Dakwah IAIN Purwokerto, 2009)
Guidance and counseling activity is and reciprocal interaction that contain mutual-influence relation between counselorand client. Counselor have role as individual who will guide client to attain certain goal. To play this role effectively, counselor needcertain capacity that define his quality. The most important capacity is counselor’s character quality (the man behind the system).Several counselors’ character quality related with counselor’s attitude, value, behavior, and spirituality. These qualities have utmostpriority at counselor’s education phase. Therefore, counselor needs a character training that have psycho-spiritual-education feature